2023
DOI: 10.3390/ma16020844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Size Distribution of Standard Sands on the Physical-Mechanical Properties of Mortars

Abstract: Obtained natural sands can present different particle size distributions (PSD), although they have the same mineralogical origin. These differences directly influence the physical and mechanical behavior of mortars and, therefore, the performance of mortar and ceramic renderings. Standardizing the particle size of sands based on pre-established requirements in normative standards (NBR 7214 or ASTM C778) is one way to minimize these effects. However, these standards do not consider the optimization of the granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that reducing sand particle size can enhance the mechanical strength of gypsum-cemented materials [4]. In the domain of mortar properties and characteristics, a study on alkali-activated mortar employing various binder systems revealed that the mortar's workability was influenced by both the type and quantity of binder used [5]. Similarly, another study on mortar and concrete properties utilizing machine-made sand from tunnel slag emphasized the impact of sand particle size and shape on mortar IOP Publishing doi:10.1088/1755-1315/1296/1/012002 2 workability [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that reducing sand particle size can enhance the mechanical strength of gypsum-cemented materials [4]. In the domain of mortar properties and characteristics, a study on alkali-activated mortar employing various binder systems revealed that the mortar's workability was influenced by both the type and quantity of binder used [5]. Similarly, another study on mortar and concrete properties utilizing machine-made sand from tunnel slag emphasized the impact of sand particle size and shape on mortar IOP Publishing doi:10.1088/1755-1315/1296/1/012002 2 workability [6].…”
Section: Introductionmentioning
confidence: 99%